GPS-RTK signal analysis conception in application to monitoring of engineering structures = Koncepcja analizy sygnałów GPS-RTK w zastosowaniu do monitoringu obiektów inżynierskich - Gil, Józef (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents a concept for analysis of GPS-RTK (Real Time Kinematic) observations in the aspect of monitoring engineering objects, exposed to deformation. It describes the on-line adaptation algorithm for the blind separation of two statistically independent signals, representing changes of the modules of "zero" vector. In order to isolate particular oscillations (trend, periodicity) from the signals observed, the exponential equalization of signals was carried out by means of the algorithm of exponential average weights, then the counter-propagation algorithm was used, which, as a vector classifier, eliminated rudimentary noise and disturbances. On that basis it was estimated that GPS signals are inharmonious cyclic signals whose basic harmonious components estimated determine the fundamental changes of the modules of the "zero" vectors.
Keywords: GPS; analiza sygnałów; monitorowanie obiektów inżynierskich; signal analysis GPS-RTK; neural networks